COST Action 625 Results: Monitoring of the Kaparelli fault, 2003-2006 - Ganas, A.; Drakatos, G.; Bosy, J.; Petro, L.; Kontny, B.; Stercz, M.; Melis, N. S.; Cacon, S.; Papanikolaou, M.; Pirentis, A.; Kiratzi, A. (Bulletin of the Geological Society of Greece, 2007)
Since November 2003 a collaborative group between Greek, Polish, and Slovak colleagues installed a dense network of non-permanent GPS stations and extensometers to monitor active faults in the eastern end of the Gulf of Corinth, central Greece. The network includes eleven GPS stations across the Kaparelli fault and the Asopos rift valley to the east and two TM-71 extensometers that were installed on the Kaparelli fault plane. The motions recorded by the TM-71 instruments show agreement with long-term fault kinematics. The GPS network has been measured in three campaigns (2004, 2005 & 2006) with very good accuracies (1-4 mm in the horizontal plane). Given that the total offset on the Kaparelli fault is small, and the geological data suggesting a segmented character of this fault, we expect in the near future to differentiate fault slip and strain accumulation among segments.